PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION DI CV. YAMAHA WAJA MOTOR DENPASAR - Komang Ayu Indah Pratiwi; Ni Nyoman Suryani; I Nyoman Mustika (VALUES, 2021)
Yamaha Waja Motor Denpasar, is a special Yamaha Motorbike Dealer company with 35 employees. The results of the author's observation and interviews with HRD at CV. Yamaha Waja Motor Denpasar obtained information that the occurrence of employee Turnover Intention which can be seen from the inconvenience of employees at work, frequently violated time discipline, absent from work without reason and the absence of cooperation and participation of all employees in solving problems. The high employee turnover rate occurs because most of them feel that the workload is excessive, so companies must also pay attention to how to maintain and manage employee workloads. The occurrence of work Bebans due to certain targets given by employees in completing work becomes a workload that can be experienced by employees. Based on the results of research and discussion results, it can be concluded as follows: Workload has a positive and insignificant effect on employee turnover intentions. This can be seen from the significance value of the t test = 0.558> 0.05 (5%). Job Bebans has a positive and significant effect on Turnover Intentions of employees at CV. Yamaha Waja Motor Denpasar. This can be seen from the results of the t-test, the significance of the t-count for the variable work Bebans (X2) is 0.000 <0.05 (5%)